PERFORMANCE EVALUATION OF SOLAR PHOTOVOLTAIC PANEL MOUNTED ON SLOPED CORRUGATED METAL SHEET ROOF IN KANO STATE NORTHWEST NIGERIA - Abdullahi Abdulkadir Aliyu; Abdullahi, Bala; Tambaya, Magaji; Ahmed, Abdullahi; Tukur, Ibrahim Aliyu (FUDMA JOURNAL OF SCIENCES, 2023)
Installation of solar photovoltaic system on roof has advantages of proper utilization of space, help in avoiding shading effects and reduction of dust accumulation on the panels. However, electrical efficiency and lifespan of solar photovoltaic panel tends to decrease due to the increase in surface temperature above the operation temperature of the panels due to its contact with the roofing sheets. The performance of solar photovoltaic panels was experimentally investigated on   corrugated metal sheet (CMS) roof at four different heights (0, 100, 200, and 300mm). Four polycrystalline silicon photovoltaic panels of 10 watts each were selected from the same manufacturer. The temperatures on the roof and on the photovoltaic panels’ surfaces were measured at different solar hours. Also, the outputs of the solar panels together with the irradiance available were measured at same hours using an electronic data logger and imported to an Excel software.  Irradiance variation, gap between roof and photovoltaic panels, and heating effect on panels were found to be the parameters affecting the photovoltaic system’s performance. The highest temperature attained by the photovoltaic panel is when it was directly mounted on the roof as 76.5°C while the other photovoltaic panels mounted at a gap height of 100mm, 200mm and 300mm attained the highest temperature of 71.8oC, 69,6oC and 68.0oC respectively. The panels’ extra heat was originating from CMS roof vicinity. Output powers from the panels were unequal throughout the experiment whilst exhibited similar behavior. The panels’ temperature dropped...
Keywords: Photovoltaic System; Corrugated Metal Sheet Roof; Photovoltaic Panel; Solar Radiation; Power Output